A case report about eosinophilic enteritis presenting as abdominal pain. Issue 39 (1st October 2021) - Zhang, Hairong; Ma, Cuimei; Xue, Yuan; Hu, Zongjing; Xu, Zhen; Wang, Yibo; Zhou, Guangxi
Abstract: Rationale: Eosinophilic enteritis (EE) is an immune-mediated antigen-driven disease that may lead to clinical symptoms and organ dysfunction and characterized by the presence of extensive eosinophilic infiltrates on histopathological examination of the intestinal mucosa. Patient concerns: A 29-year-old man presented with a half-month duration of paroxysmal upper abdominal pain that gradually evolved into continuous pain accompanied by the urge to defecate. Diagnoses: Pathological findings of enteroscopy showed acute and chronic inflammation accompanied by eosinophilic infiltration (>20/ high-power field). Interventions: The patient was initially treated with IV infusion of dexamethasone 10 mg per day for 3 days, which was reduced to 7.5 mg per day for 2 days once pain relief was achieved. Upon discharged from our hospital, the patient was prescribed with oral prednisolone 30 mg per day, which was reduced by 5 mg per week for 6 weeks until discontinuation. Outcomes: The patient was relieved from the pain after receiving dexamethasone for 5 days, and he was maintained on oral prednisolone 30 mg per day upon discharge from the hospital. On the day of discharge, the eosinophil count and derived ratios were normal. Lessons: In patients with EE, the dynamic changes of the eosinophil count should be monitored. Clinicians must be aware that not all patients with EE have a history of allergies. In the management and treatment of the disease, multisite biopsies should be carried out if EE is suspected, and EE is responsive to steroid therapy.